Robotics and AI as Resources for Teaching Geometry in Argentine Secondary Schools - Parra, Verónica; Corica, Ana; Toloza, Juan Manuel; Berdún, Luis; Schiaffino, Silvia; Godoy, Daniela (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2025: Anais do XVII Simpósio Brasileiro de Robótica e XVI Workshop de Robótica na Educação, 2025)
This work presents a proposal for Geometry teaching in secondary schools in Argentina using robotics and Artificial Intelligence (AI) as class resources. This proposal is materialized via a Mathematics problem that involves concepts such as distance, symmetry and turn angles. The algebraic solution to this problem, in its most general version, is complex for the secondary school level, since it involves two variable functions and their derivatives. However, a simplified version can be used at this level enabling the use of robots to explore the problem as well as to provide a solution in the learning context and according to the background of students.